As ações em educação ambiental realizadas por Organizações Não-Governamentais no estado de São Paulo: alcances e limitações - Fossaluza, André Santachiara [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The acting of Non-Governmental Organizations (NGOs) especially on environmental and educational fields have grown and become more emblematic during the last decades. Despite the several efforts to analyze the quality of the actions on environmental education developed by them, there is not a relevant amount of researches tha broadly and deeply analyze these issues. Thus, this work aimed to identify and list the Environmental Non-Governmental Organizations (ENGOs) in São Paulo state, identify which of them develop actions on environmental education and analyze those actions based n the Historical-Critical Pedagogy and critical conceptions of environmental education. As research methods, we collected and analyzed documents and conducted semi-estructured interviews based on Content Analysis. We found 276 ENGOs in São Paulo state, among which 175 perform environmental education actions; 44 of these acting ENGOs were interviewed to collect quantitative and qualitative data. The results show the environmental education activities performed by ENGOs in São Paulo state tend to be conservative, isolated and supported by the 1º and 2º sectors of society. The organization of the ENGOs tends to be democratic. Our results agree with the debate which has been brought by other studies and provide empirical data to suggest that the educational work developed by the ENGOs is wide. However, it tends to be qualitatively limited and bring small contribution to create and ecologically balanced and socially fair society when we consider the critical theoretical framework we take for education and envirnmental education

A atuação de Organizações Não-Governamentais, especialmente na área ambiental e educacional, tem crescido e se tornado mais emblemática nos últmos anos. Apesar de diversos esforços para analisar a qualidade das ações em educação ambiental por elas desenvolvidas, ainda é necessária a realização de trabalhos que as analisem de forma ampla e aprofundada. Por essa razão, o presente trabalho teve como objetivos mapear as Organizações Não-Governamentais (ONGs) Ambientalistas do estado de São Paulo, identificar quais delas realizam ações em sob o prisma das concepções críticas da educação ambiental e da Pedagogia Histórico-Crítica. Como procedimentos de pesquisa, coletamos documentos e realizamos entrevistas semiestruturadas, ambos analisados com base na Análise de Conteúdo. Encontramos 276 ONGs Ambientalistas no estado, das quais 175 realizam ações em educação ambiental; 44 dessas organizações foram entrevistadas para coleta de dados de ordem quantitativa e qualitativa. Os resultados mostraram que as atividades em educação ambiental realizadas por ONGs Ambientalistas no estado de São Paulo tendem a ser conservadoras e pontuais. Além disso, são majoritariamente financiadas pelos chamados 1º e 2º setores da sociedade. Sobre a organização estrutural das ONGs Ambientalistas, os dados mostram que elas tendem a ter gestão democrática e autogestionária. Nossos resultados corroboram com o debate trazido em trabalhos anteriores e fornece dados empíricos para sugerir que o trabalho educacional desenvolvido pelas ONGs tende a ser, apesar de amplo, limitado, e segundo os referenciais críticos de educação e educação ambiental adotados, tendem a contribuir pouco para a criação de uma sociedade ecologicamente equilibrada e socialmente justa, na perspectiva de sua transformação
The actions on Environmental education conduced by Non-Governmental Organizations in SãoPaulo State: reaches and limits
Keywords: Educação ambiental; Organizações não-governamentais - São Paulo (Estado); Pedagogia critica; Ambientalismo; Environmental education